Pelatihan Takhrij Hadis Sebagai Upaya Peningkatan Kompetensi Penelitian Mahasiswa Dalam Dunia Digital - Lutfianto, Mohammad; Taqwallo; Sa’diyah, Fatichatus (PT. Cahya Edupreneur Indonesia, 2025)
The development of the capabilities of students in the Hadith Studies Program at STIU Darussalam Bangkalan through mentoring and training in digital takhrīj is designed to address their low digital literacy and conventional takhrīj skills. This study employs a Participatory Action Research (PAR) approach with a descriptive qualitative design, involving 25 student participants. Data were collected through participatory observation, semistructured interviews, pre and posttests, and analysis of digital takhrīj reports. The results indicate an average increase of 25 points from pretest to posttest, with 80 % of participants able to independently understand and apply digital takhrīj methods. The implementation of thematic takhrīj enabled students to trace and classify hadiths according to specific topics and to visualize the sanad network using network analysis. These findings demonstrate the effectiveness of blended learning and PAR in accelerating the hadith research process and expanding interdisciplinary insights. It is recommended that digital takhrīj modules be integrated into the curriculum to sustain capacity building.